Application Of Fuzzy Multidimensional Association Rule For Analysis The Feasibility Of Granting Credit Plus To Prospective Customers ( Studi Kasus : PT. ”X ” Cabang Bangkinang ) - Erni Rouza (RJOCS (Riau Journal of Computer Science), 2016)
PT. “X” Bangkinang branch in analyzing the feasibility of granting credit to prospective customers, are still using manual means with consideration of the results of the survey and the amount of salary prospects. With so many potential customers who apply that credit, the PT. “X ” Bangkinang branch having difficulty in making the right decision and quickly, therefor required an application that simultaneously can be used to processing the data, analyze the feasibility and send credit recommendations quickly, efficiently, and accurately. In this final, Fuzzy Association Rule is a method that is implemented for the recommendation whether or not potential customers were given credit by using several criteria which is, age, occupation, salary amount, character, security level salary and has a house or not, appropriate decisions based on rules recommended -rule or knowledge resulting from calculating the value of support, and confidence value of each first pattern grouped within a certain interval called the fuzzy sets. From the test results can be concluded that the method of fuzzy association rulemay result in the rules or knowledge to help the Credit analysts (CA) in decision-making prospects who deserve credit approval, but these systems do not have a dynamic menu that can add or reduce other supporting criteria for consideration of recommendations.